Pengaruh Disiplin, Motivasi Kerja Dan Kerjasama Tim Terhadap Kinerja (e-Kinerja) DiKantor Polsek Ngantru Kabupaten Tulungagung - Sumaji, Sumaji; Arisyahidin, Arisyahidin; Rusandy, Deby Satyo (REVITALISASI : Jurnal Ilmu Manajemen, 2024)
The purpose of this research is to know and analyze the influence of discipline, the team work and cooperation on performance in ( e-kinerja ) Ngantru Police Tulungagung District. This study using descriptive quantitative methods. With a population and those members of the Police Ngantru District Tulungagung totaling 28 respondents. A method of collecting the data using a questionnaire, literature and methods of observation field. While the data analysis using analysis linear regression. The results of this study show that discipline, work motivation and teamwork against performance (e-kinerja). It is supported by the result of r square or coefficient determination (KD ) shows 83.8 % so interpreted if variable X1 (work discipline ), X2 (work motivations) and X3 (team cooperation ) have a contribution of 83.8 % to variable Y the performance (e-kinerja ) and 16.2% others are influenced by other factors besides variable X. In addition, in the f count 18,077 receive is worth of 0,000 sig. Thus showing that the f count greater than f table or 18,077 > 2,99 with the sig 0,000< 0,05 Thus received hypothesis, while on the outcome of the t known for partial that discipline, the team work and cooperation on performance ( e-kinerja ) Ngantru Police Officer At Tulungagung District.